Conglomeration of biliary atresia–induced pediatric biliary cirrhosis and nodular transformation–driven circulatory remodeling– A systematic review. - Subramani, Dr. Priyadarshini; Shunmugavelu, Dr. Karthik (Student's Journal of Health Research Africa, 2023)
Background Biliary atresia (BA) is a progressive fibro-inflammatory cholangiopathy of infancy that rapidly advances to biliary cirrhosis. In advanced disease, pseudolobular architecture and nodular transformation are accompanied by marked alterations in hepatic microcirculation. These vascular changes contribute to portal hypertension and early decompensation. Objective: To systematically evaluate published evidence on nodular transformation–driven circulatory remodeling in biliary atresia–induced pediatric biliary cirrhosis and its clinical implications. Methods A systematic review was conducted following PRISMA guidelines. PubMed/MEDLINE, Embase, Scopus, Web of Science, and LILACS were searched for studies published between 2020 and 2024 using predefined Boolean terms related to biliary atresia, cirrhosis, nodules, and hepatic pathology. Eligible studies included original research articles, case series, and clinicopathologic investigations addressing vascular remodeling, nodular transformation, or microvascular alterations in BA-related cirrhosis. Review articles, editorials, and studies unrelated to pediatric BA were excluded. Study quality was assessed using the STROBE checklist. Results Six studies met the inclusion criteria. Histopathological analyses demonstrated that bile duct proliferation, portal inflammation, and progressive fibrosis correlate with cirrhotic transformation after Kasai hepatoportoenterostomy. Explant-based studies reported a high prevalence of hepatic nodules, with a subset showing dysplastic or malignant potential. Radiologic-pathologic correlations identified portal vein hypoplasia with compensatory hepatic arterial enlargement, supporting arterialization of cirrhotic lobules. Emerging imaging modalities, including phase-contrast computed tomography, provide three-dimensional characterization of sinusoidal remodeling and altered inflow–outflow dynamics. Conclusion BA-induced pediatric biliary cirrhosis is characterized by nodular transformation accompanied by portal flow reduction and compensatory arterial remodeling. These structural and hemodynamic alterations underpin early portal hypertension and justify intensified surveillance strategies in children surviving with native livers.